2022
DOI: 10.1039/d2py00567k
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of eight-arm tapered star copolymers prepared by anionic copolymerization and coupling reaction

Abstract: Tapered copolymer is one kind of copolymers with unique microstructure, whereas multiarm tapered star copolymer has been rarely studied possibly due to the synthetic challenge. Herein, this work focuses on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Moreover, block copolymers are usually formed by the connection of two or more homopolymers via covalent or noncovalent bonds. Due to the variance of the chemical structure, repulsion is generally present between different block segments [10]. When the strength of mutual repulsion reaches a certain level, it will induce microphase separation to form nanostructures with various morphologies [11], which endows them with potential applications in a wide range of areas, such as thermoplastic elastomers [12], smart materials [13], drug delivery carriers [14,15], electronics [16], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, block copolymers are usually formed by the connection of two or more homopolymers via covalent or noncovalent bonds. Due to the variance of the chemical structure, repulsion is generally present between different block segments [10]. When the strength of mutual repulsion reaches a certain level, it will induce microphase separation to form nanostructures with various morphologies [11], which endows them with potential applications in a wide range of areas, such as thermoplastic elastomers [12], smart materials [13], drug delivery carriers [14,15], electronics [16], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Anionic polymerization is still the most potent living polymerization method that can be applied to synthesize well-defined polymers with controlled molecular weights ( M n ) and extremely narrow molecular weight distributions ( M w / M n ). 1–24 However, the anionic polymerization of most styrene derivatives containing electrophilic moieties, such as ketone, ester, and imine groups, has not been successfully achieved because these highly reactive moieties are attacked by anionic initiators or carbanions of the active chain-end during polymerization. To prevent such difficulties, Ishizone et al suggested the introduction of bulky substituents onto styrene derivatives containing electrophilic groups.…”
Section: Introductionmentioning
confidence: 99%